2015
DOI: 10.1101/gr.188573.114
|View full text |Cite
|
Sign up to set email alerts
|

Organelle DNA rearrangement mapping reveals U-turn-like inversions as a major source of genomic instability in Arabidopsis and humans

Abstract: Failure to maintain organelle genome stability has been linked to numerous phenotypes, including variegation and cytosolic male sterility (CMS) in plants, as well as cancer and neurodegenerative diseases in mammals. Here we describe a next-generation sequencing approach that precisely maps and characterizes organelle DNA rearrangements in a single genome-wide experiment. In addition to displaying global portraits of genomic instability, it surprisingly unveiled an abundance of shortrange rearrangements in Arab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
78
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(87 citation statements)
references
References 42 publications
(56 reference statements)
8
78
0
Order By: Relevance
“…These Whirly family proteins share a typical DNA-binding structure (Desveaux et al, 2002) and participate in the maintenance of organellar genomes. Recent work demonstrated that a double knockout of AtWHY1 and AtWHY3 results in chloroplast defects due to illegitimate recombination in the plastid genome (Maréchal et al, 2009;Lepage et al, 2013), and AtWHY1 and AtWHY3 appear to stabilize the plastid genome by repressing short-range rearrangements (Zampini et al, 2015). Structural analysis also indicated that AtWHY2 binding may stabilize mtDNA to favor accurate repair of DNA double-strand breaks (Cappadocia et al, 2010).…”
Section: Atwhy2 Alters Mtdna Copy Numbersmentioning
confidence: 99%
“…These Whirly family proteins share a typical DNA-binding structure (Desveaux et al, 2002) and participate in the maintenance of organellar genomes. Recent work demonstrated that a double knockout of AtWHY1 and AtWHY3 results in chloroplast defects due to illegitimate recombination in the plastid genome (Maréchal et al, 2009;Lepage et al, 2013), and AtWHY1 and AtWHY3 appear to stabilize the plastid genome by repressing short-range rearrangements (Zampini et al, 2015). Structural analysis also indicated that AtWHY2 binding may stabilize mtDNA to favor accurate repair of DNA double-strand breaks (Cappadocia et al, 2010).…”
Section: Atwhy2 Alters Mtdna Copy Numbersmentioning
confidence: 99%
“…However, such signatures are not found in the indels identified in this study (Supplemental Data Set 1). Furthermore, no plastome rearrangements suggesting MMBIR repair (Cappadocia et al, 2010) or U-turn-like inversions (Zampini et al, 2015) were found. One possible exception is the large 1364-bp deletion in the mutant V-delta, which is not associated with a repetitive element (Supplemental Figure 6).…”
Section: Spontaneous Mutations Are Largely Limited To Replication Slimentioning
confidence: 99%
“…In the corresponding mutants, there is reduced repair by homologous recombination and there might be increased illegitimate recombination involving sequence microhomologies (Cappadocia et al, 2010;Parent et al, 2011;Janicka et al, 2012;Miller-Messmer et al, 2012). These illegitimate recombination events are possibly responsible for U-turn genomic inversions that accumulate in plant organelles and also in human mitochondria (Zampini et al, 2015).…”
Section: Introductionmentioning
confidence: 99%